Developing a Multiliteracy Learning Model Based on Malangan Masks to Enhance Cultural Literacy and Global Diversity in Elementary Students - Mellyaning Khoiriya, Rika; Mudiono, Alif; Barus, Yohannes Kurniawan; Sari, Novanda Nurisma; Attila, Zulfikar; Hidayati, Rizqiya Putri (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Abstract: This study aims to develop a multiliteracy learning model based on Topeng Malangan literature to improve literacy culture and global diversity attitude in grade IV elementary school students. This study used the ADDIE research and development method, which involved fourth-grade students at SDN Talangagung 2 Kepanjen. Data were collected through expert validation, student and teacher responses, observation, and literacy skills tests. The results showed the model's effectiveness in improving students' literacy skills with a high level of interest (80-92.3%) and understanding of the material (84.6-86.67%). The model also successfully developed students' global diversity attitudes, with 80-92.3% reporting increased knowledge. Expert validation covering readability, material suitability, and learning aspects in elementary schools showed excellent results with scores of 90.90%, 88.33%, and 86.42%, respectively. The learning model received excellent effectiveness ratings, with 91.40% and 92.47% in the two classes studied. This research contributes significantly to developing innovative and contextualized Indonesian language learning strategies at the primary school level by integrating local wisdom and multiliteracy approaches to improve literacy skills and cultural understanding.